Contrast media induced transient cortical blindness - Balasingam, S.; Azman, R.R.; Nazri, M. (Oxford University Press, 2016)
Extract: A 60-year-old man who had previous coronary artery bypass graft surgery with a left internal mammary artery (LIMA) graft, underwent a coronary angiogram to investigate multiple episodes of angina. His only other significant past medical history was well-controlled hypertension. The patient was previously exposed to iodinated contrast media with no history of reaction. His pre-procedural blood pressure and renal function was noted to be normal. No premedication was used. During injection of the LIMA, the patient complained of blurring of vision which deteriorated to near total blindness within minutes. On examination, the patient was able to only differentiate light from dark and unable to do finger counting. The pupils were equal in size and responsive to light. The rest of the neurological examination was normal. The...